Dilema moral na Educação Infantil: generosidade ou justiça? - Kawashima, Rosana Akemi [UNESP]; Martins, Raul Aragao [UNESP] (My University, 2013)
The aim of this study is to investigate the judgments about the virtue of generosity or justice by teachers in early childhood education and compare their judgments with the children’s judgments about generosity or justice. We interviewed 26 teachers and 90 children aged 4, 5 and 6 years at this level of education. The instrument used was a moral dilemma in which the protagonist of the story would have to choose between giving a prize to the child who drew the most beautiful picture (justice) or to the child who was sad (generosity). The results indicate that justice is the virtue most valued by teachers and that it is already valued by children and may be a need for them. And generosity is valued more by children than by teachers.

O objetivo deste trabalho é investigar os juízos a respeito da virtude generosidade ou justiça de professores da educação infantil e compará-los com os das crianças. Foram entrevistados 26 professores e 90 crianças de 4, 5 e 6 anos de idade desse nível de ensino. O instrumento utilizado foi um dilema moral em que a protagonista da história teria de optar entre dar um prêmio para a criança que fez o desenho mais bonito (justiça) ou para a criança que estava triste (generosidade). Os resultados indicam que a justiça é a virtude mais valorizada pelas professoras e que já é valorizada pelas crianças, podendo ser uma necessidade para elas. E a generosidade é mais valorizada pelas crianças do que pelas professoras.
Keywords: generosidade; justiça; educação infantil; valores morais; generosity; justice; early childhood education; moral values